Factor Structure of the Italian Version of the Religious Fundamentalism Scale. Issue 1 (February 2013) - Carlucci, Leonardo; Tommasi, Marco; Saggino, Aristide
The Religious Fundamentalism Scale was applied to an Italian group, composed of 250 participants, to assess if it could be considered a reliable measure of fundamentalism. All participants professed to be believers of the Catholic religion. The overall group was split randomly into two smaller groups. The data of the first group were analyzed with an exploratory factor analysis (EFA) to test the factor structure of the Italian version of the scale. The data of the second sample were analyzed with a confirmatory factor analysis, to test the factor structure that emerged from EFA. Results indicated a two-dimensional structure, composed of two correlated factors apparently representing believing and skeptical attitudes.